PENGGUNAAN MEDIA SOSIAL INSTAGRAM DAN LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF BERBELANJA ONLINE GENERASI MILENIAL - Susanti, Ari; Rikah, Rikah (JAB (Jurnal Akuntansi & Bisnis), 2020)
ABSTRACTÂ Increased internet usage Required for instagram specific social media increases in millennial generation so research is needed whether millennial financial literacy in the use of social media influences consumptive behavior. This research deals with objectives relating to social media, finance for perliaku behavior. Responding in this study the replacement of 100 of the generations that match the criteria specified in this study. The results of this study prove that Social Media (X1) and Financial Literacy (X2) influence consumer behavior (Y) in millennial generation. This is because the generation is concerned with the desires of the needs.Â Keywords: Social Media, Financial Literacy and consumptive behavior